2022
DOI: 10.1109/access.2022.3179108
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sizing of Onboard Hybrid Energy Storage Devices Considering the Long-Term Train Operation

Abstract: With the fast development of energy storage technology, more applications of Energy Storage Devices (ESDs) have been found in rail transportation in recent years. This paper aims to address the optimal sizing problem of on-board Hybrid Energy Storage Devices (HESDs) which are installed to assist train traction and recover the regenerative braking energy. On-board HESDs combining Li-ion battery and supercapacitor can further enhance the capacity and instant power rating. In this paper, a mixed integer linear pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Many researchers have found that the use of on-board HESDs allows for a more flexible system, where SCs and Li-ion BATs can improve the power density and energy density of the integrated system, respectively [19,39,40]. After considering the optimized scenarios and commonly used commercial components, the proposed integrated system in this work is mainly composed of: (1) each cell for Li-ion BATs is 10 Ah and 2.3 V. When the rated charge/discharge rate is 4 C, the rated charging power is −93.3 W and rated discharging power is 93.3 W [22]; (2) each module for BMOD0063-P125-B08 supercapacitor is 63 F, which is specifically designed for heavy transport applications such as electric trains, trolleys, cranes, etc.…”
Section: The System Setup Of the Electric Train With On-board Hesdsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many researchers have found that the use of on-board HESDs allows for a more flexible system, where SCs and Li-ion BATs can improve the power density and energy density of the integrated system, respectively [19,39,40]. After considering the optimized scenarios and commonly used commercial components, the proposed integrated system in this work is mainly composed of: (1) each cell for Li-ion BATs is 10 Ah and 2.3 V. When the rated charge/discharge rate is 4 C, the rated charging power is −93.3 W and rated discharging power is 93.3 W [22]; (2) each module for BMOD0063-P125-B08 supercapacitor is 63 F, which is specifically designed for heavy transport applications such as electric trains, trolleys, cranes, etc.…”
Section: The System Setup Of the Electric Train With On-board Hesdsmentioning
confidence: 99%
“…Although the researchers in our group have published some works on distance-based MILP models [19,35,37], which have been proved to have excellent robustness and fast optimization characteristics, heavy computational burdens are obtained when calculating the nonlinear constraints, especially the derivation of SOC for on-board HESDs and product operation of multiple time-varying parameters. Alternatively, as shown in Figure 2, the discretization process of the proposed, time-based MILP model is revealed, where each time segment ∆t is a known parameter and the distance S i (i = 1, 2, 3 .…”
Section: Optimization and System Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Their case study shows the train equipped with on-board ESS can save 14.2% of total energy consumption. Others use various optimization methods to determine the capacity of on-board ESS for train [33]- [35].…”
Section: Regenerative Braking Utilization In Dctps By Storage Devicementioning
confidence: 99%